Function focused care in hospital: A mixed-method feasibility study - Selma Kok; Janneke M. de Man-van Ginkel; Carolien Verstraten; Barbara Resnick; Silke F. Metzelthin; Nienke Bleijenberg; Lisette Schoonhoven (Elsevier, 2021)
Background: During hospitalization patients frequently have a low level of physical activity, which is an important risk factor for functional decline. Function Focused Care (FFC) is an evidence-based intervention developed in the United States to prevent functional decline in older patients. Within FFC, nurses help older patients optimally participate in functional and physical activity during all care interactions. FFC was adapted to the Dutch Hospital setting, which led to Function Focused Care in Hospital (FFCiH). FFCiH consists of four components: (1) 'Environmental and policy assessment'; (2) 'Education'; (3) 'Goal setting with the patient' and (4) 'Ongoing motivation and mentoring'. The feasibility of FFCiH in the Dutch hospital setting needs to be assessed. Objective: Introduce FFCiH into Dutch hospital wards, to assess the feasibility of FFCiH in terms of description of the intervention, implementation, mechanisms of impact, and context. Design: Mixed method design Setting(s): A Neurological and a Geriatric ward in a Dutch Hospital. Participants: 56 Nurses and nursing students working on these wards. Methods: The implementation process was described and the delivery was studied in terms of dose, fidelity, adaptions, and reach. The mechanisms of impact were studied by the perceived facilitators and barriers to the intervention. Qualitative data were collected via focus group interviews, observations, and field notes. Quantitative data were collected via evaluation forms and attendance/participation lists. Results: A detailed description of FFCiH in terms of what, how, when, and by whom was given. 54 Nurses (96.4%) on both wards attended at least 1 session of the education or participated in bedside teaching. The nurses assessed the content of the education sessions with a mean of 7.5 (SD 0.78) on a 0-10 scale. The patient files showed that different short and long-term goals were set. Several facilitators and barriers were identified, which led to additions to the intervention. An important facilitator was that nurses experienced FFCiH as an approach that fits with the principles underpinning their current working philosophy. The experienced barriers mainly concern the implementation elements of the FFCiH-components 'Education' and 'Ongoing motivation and mentoring'. Optimizing the team involvement, improving nursing leadership during the implementation, and enhancing the involvement of patients and their family were activities added to FFCiH to improve future implementation. Conclusions: FFCiH is feasible for the Dutch hospital setting. Strong emphasis on team involvement, nursing leadership, and the involvement of patients and their families is recommended to optimize future implementation of FFCiH in Dutch hospitals.What is already known • Function Focused Care is an evidence-based intervention that prevents functional decline among hospitalized elderly; • It is proven to be effective in assistant living facilities, nursing homes, home care, and acute care settings in the United States; • It is unknown if the intervention can be implemented in the Dutch Hospital Setting.What this paper adds • This study showed the feasibility of Function Focused Care in Hospital and the challenges in some elements of the intervention; • Optimizing the team involvement, improving nursing leadership during the implementation, and enhancing the involvement of patients and their family were added to FFCiH to improve future implementation. • This feasibility study can guide the use of process evaluation in examining the feasibility of an intervention in daily practice.